Selection of Suitable Urban Tolling System Technology - Hrudkay, Karol (Communications - Scientific letters of the University of Zilina, 2015)
Article deals with the selection of suitableselection urban tolling system technology. In the paper, a lot of aspects, which have an influence on selection of particular technology in city conditions, were considered. For example: charging policy, user aspects, technical aspects and economic aspects. Although the analysis was not performed within specific conditions of a particular city, it was found out that in spite of general analysis, it is possible to form relevant and rather clear conclusions.